Feasibility of Using Strength Measures, Including Peak Inspiratory Flow, for Routine Monitoring in Case Management Patients Aged 65 and over - Nicola Barnes; Bronagh Walsh; Dinesh Samuel (Geriatrics, 2020)
Peak inspiratory flow (PIF) is a portable, relatively new method for measuring respiratory function and indirect muscle strength; the feasibility of its routine clinical measurement is unknown. To investigate the acceptability, reliability and short-term stability of PIF, alongside the established measures of peak expiratory flow (PEF) and grip strength in community dwelling case management patients. Patients were tested in a sitting position, initially on two occasions, one week apart; seven patients having repeated measures taken on a further four occasions over a seven-week period. The best of three attempts for all measures were recorded. Reliability was tested using intra-class correlation coefficient (ICC), standard error of measurement (SEM), minimal detectable change (MDC) and Bland–Altman analysis. Eight patients aged 69–91 years (mean age 81.5 ± 7.7 years; 5 males) participated. For between-day reliability using the first two time points, one week apart the ICCs (3,1) were 0.97, 0.98 and 0.99 for PIF, PEF and grip strength respectively; using all five time points resulted in ICCs of 0.92, 0.99 and 0.99 respectively. Bland–Altman plots also illustrated a good level of agreement across days. Feedback on the acceptability of the measures was gathered from patients. PIF, PEF and grip strength showed excellent reliability and acceptability. Whilst excellent reliability was observed over the seven-week period, the occurrence of clinically significant symptoms and adverse events in the presence of unchanging PIF, PEF and grip strength, suggests that the measures may not be suitable to identify patients with multiple health conditions entering a period of acute decline.